Mechanics of generalized continua - Altenbach, Holm 1956-; Maugin, G. A. (Gérard A.) 1944-; Erofeev, Vladimir (Advanced Structured Materials, 2011)
This collection on "Mechanics of Generalized Continua - from Micromechanical Basics to Engineering Applications" brings together leading scientists in this field from France, Russian Federation, and Germany. The attention in this publication is be focussed on the most recent research items, i.e., - new models, - application of well-known models to new problems, - micro-macro aspects, - computational effort, - possibilities to identify the constitutive equations, and - old problems with incorrect or non-satisfying solutions based on the classical continua assumptions.